Evaluation of the binding behavior of olmutinib (HM61713) with model transport protein: Insights from spectroscopic and molecular docking studies - Kou, Song-Bo; Lin, Zhen-Yi; Wang, Bao-Li; Shi, Jie-Hua; Liu, Ying-Xin (Journal of molecular structure, 2021)
•Binding behavior between olmutinib (OMT) with model transport protein, BSA was investigated.•Binding affinity between OMT with BSA is stronger with the Kb of about 105 M−1 order.•The driven forces include hydrophobic interactions, hydrogen bonds as well as van der Waals forces.•The common metal ions could promote the binding interaction of OMT with BSA.•OMT insets into the hydrophobic pocket in subdomain IB (site III) of BSA. Olmutinib (HM61713, OMT), a novel third-generation tyrosine kinase inhibitor with good orally absorption, is able to inhibit selectively epidermal growth factor receptor mutations. In this work, the binding behavior of OMT with model transport protein bovine serum albumin (BSA) was assessed with the help of spectroscopic and molecular docking approaches. A fluorescence quenching of BSA was observed during the binding interaction of OMT with BSA, followed by a static mechanism was demonstrated. The affinity of OMT with BSA was moderate due to the binding constant of 2.75 × 105 M−1 at 293 K. The hydrophobic interactions, hydrogen bonds as well as van der Waals forces were acting as the predominant contributions in the OMT-BSA complexation process. The findings from site competitive experiments revealed that OMT tended to bind to subdomain IB (site III) of BSA, which was in keep with the outcomes of molecular docking studies. Based on synchronous and 3D fluorescence studies, we found that the conformation of BSA was changed owing to the binding with OMT. The FT-IR and UV-Vis studies further corroborated that the binding of OMT to BSA changed the secondary structure of BSA. Additionally, the experimental data showed that some metal ions (e.g. Ni2+, Fe3+, Mg2+, Cu2+) could promote the binding interaction of OMT with BSA. This study is beneficial to further assess the pharmacological properties of OMT and can provide valuable reference for designing new anti-tumor drugs. [Display omitted]